Isotonic nasal spray versus fluticasone nasal spray in treatment of allergic rhinitis - Chowdary Gaddipatti, Rachana; Rao, Suman P.; Rajiv, Kalpana; Jain, Manuj (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2017)
Background: Allergic rhinitis (AR) is a prevalent disease with great morbidity and causing signiﬁcant societal and economic burden. Aims and objectives: To compare efficacy of fluticasone nasal spray and isotonic saline nasal spray in allergic rhinitis. Methods: This was a prospective randomized study conducted on patients of allergic rhinitis coming to ENT OPD a tertiary care teaching hospital. Sixty patients diagnosed with concomitant diagnosis of allergic rhinitis was randomly allocated to either Fluticasone propionate nasal spray (n= 30) and isotonic saline spray (n= 30). Results: The most common age group in fluticasone group was 21 to 30 years while in isotonic saline group 31 to 40 years was the most common age group. There was 52.8% of female and 47.2% in fluticasone group while in isotonic saline group, 52.5% of study population were female and 47.5% were male. There was significant improvement in VAS on day 15 and day 30 as compared to day 1 in fluticasone treated subjects as compared to isotonic saline group. After one month, Nasal blockage, nasal discharge, sneezing, nasal itching was improved to 71%, 69%, 81% and 78% in fluticasone treated subjects as compared to isotonic saline group in which improvement was up to 11%, 17%, 09% and 12% respectively and this difference was statistically significant. Conclusions: Fluticasone nasal spray has the potential to enhance patient satisfaction and compliance and reduce the need for polypharmacy in the management of seasonal allergic rhinitis.